Avaliação de competências de estudantes universitários de enfermagem sobre administração de vacinas no vasto lateral da coxa em crianças, utilizando o ambiente virtual de aprendizagem - Costa, Lívia Cristina Scalon Da (2018)
The administrationof vaccines intramuscularly in the anterolateral thigh muscle in children is a subject taught in undergraduate nursing in face-to-face teaching. Given the technological advances applied to education, the Virtual Learning Environment has been increasingly used to update future nurses. This study aimed to evaluate the degree of knowledge, skills and attitudes of nursing undergraduates about the administration of vaccines in the anterolateralthigh in children, as a proposal of intervention, using the Moodle Platform. Quantitative, quasi-experimental, without control group, of the pre-and post-test type performed with 39 nursing students from the 7th, 8th and 9th periods. An array of competencies has been developed to establish educational objectives. The media resources were produced: simulated scenario videos, didactic support material and discussion forum from a clinical case video. The cognitive knowledge test and the OSCE-based checklist instrument, after elaboration, were submitted to content validation and concordance analysis using the Kappa Fleiss test, with satisfactory results of the cognitive test (0,733) and the checklist of the OSCE (0,826). Three stations were created in a simulated scenario, corresponding to the three modules of the course: Station 1 -Hand Hygiene in Vaccinations Rooms, Station 2 -Preparation for administration of vaccine in the anterolateralthigh in children and Station 3 -Administration of vaccinein the anterolateral thighin children. The validation process of the simulated scenario was performed through the visit of the judges, with the aid of an instrument prepared by the author with the appropriate physical structure and the items used in a vaccination room. There was good internal consistency of this instrument according to Cronbach's Alpha (0,76). Data collection was carried out from April to June 2017. In addition to the instruments already mentioned, a questionnaire was also applied to characterize the participants, one of course evaluation, resources and strategies adopted and the COLLES Survey. Quantitative data were tabulated and analyzed using SPSS Software, version 17.0. After the pre-and post-OSCE, there was the debriefing, which consisted of the analysis and reflection on what was experienced by the student during the simulation. There was a predominance of females(87,2%), with a mean age of 24,9 years, and of participants who did not work in the nursing area. A strongly significant association was found between pre and post-test scores (p = 0,0001). We found a general mean in the pre-test of 12,5, dp= 2,56 and in the post-test of 17,4, dp= 2,38, considering a total of 21 points. It was also found a strongly significant association between the OSCE score before and after intervention (p= 0,0001), with pre-OSCE being the general average of 101,0, dp= 30,46 and post-OSCE of 181,92, dp= 12,04, considering a total of 200 points. All the media resources were very well evaluated. These results show the effectiveness of the intervention and the importance of AVA as a strategy for updating the skills of nursing undergraduates on the subject.